2016
DOI: 10.1055/s-0042-113776
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Microlithiasis: Patient Compliance in a Two-Year Follow-Up Program

Abstract: We present a retrospective 2-year follow-up cohort of 103 men with testicular microlithiasis (TML) and discuss patient compliance and the value of surveillance. A retrospective analysis of patients examined with scrotal ultrasonography (US) in the period from 2008 through 2010 was performed. A total of 103 men with TML were diagnosed and offered US follow-up every 6 months for 2 years. They were retrospectively analyzed regarding demographics and follow-up details, including the development of any kind of mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Richenberg and Brejt performed a literature study including 2656 patients referred for scrotal ultrasound examination and found 51 with TML (1.9%); none of the patients develop a germ cell tumor (11). In addition, a study investigated two-year scrotal ultrasound follow-up, including 103 patients with TML, and no cases of germ cell tumors were found (12).…”
Section: Introductionmentioning
confidence: 99%
“…Richenberg and Brejt performed a literature study including 2656 patients referred for scrotal ultrasound examination and found 51 with TML (1.9%); none of the patients develop a germ cell tumor (11). In addition, a study investigated two-year scrotal ultrasound follow-up, including 103 patients with TML, and no cases of germ cell tumors were found (12).…”
Section: Introductionmentioning
confidence: 99%
“…Subdividing according to ethnicity and prevalence in white, Asian/Pacific, Hispanic, and black men was found to be 4.0%, 5.6%, 8.5%, and 14.1% ( 1 ). Other studies have assessed the prevalence of TML in symptomatic patients to be around 8–18% ( 13 , 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subdividing according to ethnicity and prevalence in white, Asian/Pacific, Hispanic, and black men was found to be 4.0%, 5.6%, 8.5%, and 14.1% (1). Other studies have assessed the prevalence of TML in symptomatic patients to be around 8-18% (13,(18)(19)(20). Testicular macrocalcifications have only been rarely described in the literature and have typically been viewed as of no clinical significance (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In the follow-up period only 2 men (0.5%) developed testicular cancer [ 16 ]. Afterwards, Pederson et al concluded – based on the two-year follow-up program – that none of the investigated men had developed testicular cancer within the minimum time frame of 50 months [ 17 ].…”
Section: Introductionmentioning
confidence: 99%